Elements of gas turbine propulsion - Mattingly, Jack D (McGraw-Hill series in mechanical engineering, 1996)
Designed to provide an introduction to the fundamentals of gas turbine engines and jet propulsion for aerospace or mechanical engineers. The book contains sufficient material for two sequential courses in propulsion, a course in jet propulsion and a gas turbine engine components course.